Eksistensi dan Kontribusi Pondok Modern Darussalam Gontor Dalam Pembangunan Sumber Daya Manusia - Joni, Syamsuri (At-Ta'dib, 2016)
Significant development of pesantren over t he years become evidentof interest and attraction of Indonesian people to the Islamic education. Untilnow the number of pesantren in Indonesia has reached 27.218 pesantrensscattered throughout the Indonesian archipelago. The existence of pesantrensince its construct until today has contributed in various aspects of humandevelopment. Not only a religious science development institutions (tafaqquhfi al-din) that is focused internally, but also pay attention to the environmentthat kept submissive to people with its commitment (amar ma’ruf nahimunkar) in some form of character education. Therefore, pesantren are in thecenter of comunity who are born of the people by the people and for thepeople. So that education and orientation of pesantren can never be separatedfrom society. This paper will discuss how pesantren, especially Pondok ModernDarussalam Gontor Ponorogo Indonesia still exist and contribute to thedevelopment of human resources.